ANALISIS EFEKTIVITAS PROGRAM PENGENTASAN KEMISKINAN AKIBAT PANDEMI COVID-19 DI KABUPATEN PASURUAN - Achmad Miftahul Khoiri; Ulfa Binada; Bahagia Nastiti (Bappeda Kota Malang, 2022)
The high poverty rate in Pasuruan Regency caused by Covid-19 has resulted a high demand for an effective strategy from the local government. The purpose of this study is to examine the strategies to alleviate poverty caused by the Covid-19 pandemic in Pasuruan Regency. This research is a descriptive research conducted through a qualitative approach with relevant primary and secondary data sources. The results of the study found that the Pasuruan Regency government tried to improve the welfare of the poor who were affected by the Covid-19 pandemic by preparing a poverty alleviation program strategy in collaboration with the relevant agencies. The program to reduce the burden of spending and strengthen the creative economy by the Social Service and the Office of Cooperatives and MSMEs is the most effective program for the success of poverty alleviation. This study also found that identification of target groups is a prerequisite component for the success of poverty alleviation programs, and the need for more roles from stakeholders to increase the effectiveness of poverty alleviation programs. Thus, the program prepared by the Pasuruan Regency Government needs to be carried out optimally accompanied by the role of stakeholders to increase the effectiveness of the program to alleviate poverty due to the Covid-19 pandemic.